Deuterium charge exchange recombination spectroscopy from the top of the pedestal to the scrape off layer in H-mode plasmas. (25th October 2017) - Haskey, S.R.; Grierson, B.A.; Stagner, L.; Burrell, K.H.; Chrystal, C.; Groebner, R.J.; Ashourvan, A.; Pablant, N.A.
Abstract: Recent completion of the thirty two channel main-ion (deuterium) charge exchange recombination spectroscopy (CER) diagnostic on DIII-D [J.L. Luxon, Nucl. Fusion 42 (2002) 614] enables detailed comparisons between impurity and main-ion temperature, density, and toroidal rotation. Sixteen sightlines cover the core of the plasma and another sixteen are densely packed towards the edge, providing high resolution measurements of the pedestal and steep gradient edge region of H-mode plasmas. The complexities of theD_α Dα spectrum require fitting with a comprehensive model, as well as using iterative collisional radiative modeling to determine the underlying thermal deuterium ion properties. Large differences in the structure and magnitude of impurity (C^{6+} C 6+ ) and main-ion (D^+ D + ) toroidal rotation profiles are seen in the H-mode pedestal. Additionally theD^+ D + temperature can be half the value of theC^{6+} C 6+ temperature at the separatrix and shows more of a pedestal structure. Typically only the impurity properties are measured and the main-ion properties are either assumed to be the same, or inferred using neoclassical models, which require validation in the steep gradient region. These measured differences have implications for transport model validation, intrinsic rotation studies, pedestal stability, and the boundary conditions for scrape off layer and plasma material interactions studies.